Small towns and urban centers: The relationship of distance and population size to community satisfaction. Issue 4 (8th August 2019) - McKnight, Matthew L.; Gibbs, Benjamin G.; Sanders, Scott R.; Cope, Michael R.; Jackson, Jorden E.; Park, Paige N.
ABSTRACT: In past research, the relationship between population size and community satisfaction have reported mixed results. Additionally, few community studies utilized distance from urban centers as a complementary to population size. Using the 2010 Montana Health Matters Study, this research seeks to uncover how these two measures together help to explain community satisfaction. Our results indicate that distance and population size are conflated measures when used separately. Yet, when used together, both measures complement each other in capturing place-based elements of community satisfaction. Paradoxically, findings show that residents are less satisfied the farther they live from urban centers when accounting for population size, yet residents are more satisfied with their community when they live in very small populated communities after accounting for distance. These findings suggest that residents living in small-populated communities adjacent to urban centres are the most satisfied with their communities than larger rural communities farther from urban centers.